PENGARUH PENGGUNAAN MEDIA SOSIAL FACEBOOK TERHADAP MOTIVASI BELAJAR MAHASISWA FISIP UNIVERSITAS RIAU - Hanafi, Muhammad; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Many social networking sites can be a place to share information and with interesting features but it also can become a means of getting a lot of friends to arrive to find a mate. Internet sites such as Twitteer, Friendster, Hi5, Myspace, YouTube, Blogger and many more. Facebook is a social networking website that is now increasing in popularity and the number of members increased sharply in a short time.The main task of the student is learning and studying, because adolescence is a time of transition that is eager to note, facebook is a website that can make teens more expressive highlight himself, his desire, and profile. Thus these students will continue to play facebook that disturbed his homework and make the time taken up by a lot by playing these sites.The concept of the theory that the researchers use a communication model Stimulus - Response. To determine the stimulus arising from a sale effectively, required knowledge of the factors that influence a person to receive, consider the information and make a decision to buy the products offeredThis research is a quantitative research. To measure the force between two variables, namely social media facebook as an independent variable and learning motivation of students as the dependent variable, used simple regression, or often called simple regression.From t test results obtained value for the variable t¬test Social Media facebook3.900 (greater than ttabel 1.984), and pvalue of 0.000 <0.05), the results of this study indicate that social media facebook affect student learning motivation FISIP Riau University ,Keywords: Social Media and Motivation